2017
DOI: 10.1021/acsnano.7b03943
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Biexciton Quantum Yields and Carrier Dynamics of Quasi-Two-Dimensional Core/Shell Nanoplatelets

Abstract: Quasi-two-dimensional nanoplatelets (NPLs) possess fundamentally different excitonic properties from zero-dimensional quantum dots. We study lateral size-dependent photon emission statistics and carrier dynamics of individual NPLs using second-order photon correlation (g(τ)) spectroscopy and photoluminescence (PL) intensity-dependent lifetime analysis. Room-temperature radiative lifetimes of NPLs can be derived from maximum PL intensity periods in PL time traces. It first decreases with NPL lateral size and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 62 publications
9
112
1
Order By: Relevance
“…Among these, CdSe/CdS core/shell NPLs have been increasingly attractive due to their excellent shell‐thickness‐dependent optical performance . CdSe/CdS NPLs are synthesized with higher quantum yields (QYs) and stability as compared to CdSe core‐only NPLs, because of the effective passivation of surface trap states by the epitaxial growth of a wider bandgap shells . In addition to the passivated surface defects, the absorption cross section of CdSe/CdS NPLs was boosted owing to the intrinsically increased optical absorption of the CdS shells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, CdSe/CdS core/shell NPLs have been increasingly attractive due to their excellent shell‐thickness‐dependent optical performance . CdSe/CdS NPLs are synthesized with higher quantum yields (QYs) and stability as compared to CdSe core‐only NPLs, because of the effective passivation of surface trap states by the epitaxial growth of a wider bandgap shells . In addition to the passivated surface defects, the absorption cross section of CdSe/CdS NPLs was boosted owing to the intrinsically increased optical absorption of the CdS shells .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the passivated surface defects, the absorption cross section of CdSe/CdS NPLs was boosted owing to the intrinsically increased optical absorption of the CdS shells . At the same time, the inorganic shells could help to suppress the rapid nonradiative Auger recombination (AR) of excitons with lower Auger rates and much reduced emission intermittency at single particle level, thereby enabling to realize low‐threshold (≈6 µJ cm −2 ) amplified spontaneous emission (ASE) and obtain high threshold for gain saturation . Generally, the epitaxial growth of semiconductor shells in core/shell hetero‐nanoplatelets is performed via the colloidal atomic layer deposition (c‐ALD) method .…”
Section: Introductionmentioning
confidence: 99%
“…[35] Figure S5, presenting the PL intensity for NPLs versus excitation power, demonstrates that saturation does not occur even at the highest pulse energy of respectively. [8] , [36], [37] While the average population for the larger samples approaches saturation, the biexciton population is still substantially smaller than that of the single excitons.…”
Section: Resultsmentioning
confidence: 99%
“…[7] In contrast, due to the mean value of the lateral separation of excitons in a NPL, Auger rates are substantially lower than in QDs and the biexciton QY (BXQY) can approach that of the single exciton state. [8] Previous studies concluded that since the electron-hole binding energy in NPLs is much higher than the lateral confinement energy, Auger recombination thus occurs through exciton-exciton collisions. [9] Using ensemble experimental approaches, such as time-resolved photoluminescence (PL) and transient absorption, Li et al concluded that the rate of Auger relaxation decreases linearly with increasing the NPL lateral area and is inversely proportional to d 7 , where d is the thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Ma et al demonstrated the giant oscillator effect existed in CdSe NPLs . Unlike the 0D nanocrystals, the exciton oscillator strength in NPLs is not only related to the degree of spatial overlap between the electron–hole wavefunctions, but also increased with the area of the exciton coherent motion, which is equivalent to the NPL's lateral size.…”
Section: Exciton Behavior Of Nanoplateletsmentioning
confidence: 99%